Spring phenology in photosynthesis control and modeling for a temperate bog - He, Hongxing; Moore, Tim; Lafleur, Peter; Sonnentag, Oliver; Humphreys, Elyn; Wu, Mousong; Roulet, Nigel (Frontiers in Environmental Science, 2025)
Predicting the carbon dynamics of northern peatlands requires adequate representation of the vegetation phenology in terrestrial biosphere models. In this study, we analyzed the relative importance of various environmental controls to explain the start of the growing season through photosynthetic CO2 uptake for a temperate continental bog; accordingly, we used a multiyear measured dataset comprising eddy covariance (EC), supporting environmental measurements, and a digital image archive obtained using repeat photography. The vegetation in the studied bog is dominated by “evergreen” shrubs and mosses. The vegetation phenological indices data, including enhanced vegetation index, normalized difference vegetation index, and green chromatic coordinate, showed high correlations with the gross primary productivity (GPP) of the ecosystem obtained from EC measurements, near-surface soil temperatures, and the growing degree-day sum (∑GDD). We developed a new phenology scheme in the process-based CoupModel using ∑GDD to represent the gradual greening of the evergreen shrubs that regulate spring photosynthesis turn-on and increase. The new model simulates the earlier photosynthesis turn-on of the mosses and photosynthesis onset of the shrubs from days with ∑GDD = 50°C. Model simulations incorporating the new phenology subroutine for two vegetation layers (shrubs and mosses) show improved agreement with the daily EC-derived GPP. Our results show that when the spring phenology is not explicitly factored in, the CoupModel overestimates GPP by 24% and MODIS GPP by 45% at the end of the spring season. The results from this study are expected to advance our understanding of ecosystem dynamics and provide a foundation for refining ecosystem models to better capture the intricate interplay between phenology, carbon dynamics, and environmental conditions.